2020
DOI: 10.3390/atmos11121309
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Assessment and Temperature Study from the Interlaboratory Application of the WLTP–Brake Cycle

Abstract: The relative contribution of brake emissions to traffic-induced ambient Particulate Matter (PM) concentrations has increased over the last decade. Nowadays, vehicles’ brakes are recognised as an important source of non-exhaust emissions. Up to now, no standardised method for measuring brake particle emissions exists. For that reason, the Particle Measurement Programme (PMP) group has been working on the development of a commonly accepted method for sampling and measuring brake particle emissions. The applied b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Light braking (regime 1) is characteristic of urban driving, while heavy braking (regime 2) is characteristic of rural and highway driving. 51 The brake torque and rotor temperatures in the braking regimes adopted in the present study in general compare well with those reported as typical for some common make and model vehicles. 52 The maximum temperatures reached in each experiment are shown in Table S2 †.…”
Section: Methodssupporting
confidence: 82%
See 1 more Smart Citation
“…Light braking (regime 1) is characteristic of urban driving, while heavy braking (regime 2) is characteristic of rural and highway driving. 51 The brake torque and rotor temperatures in the braking regimes adopted in the present study in general compare well with those reported as typical for some common make and model vehicles. 52 The maximum temperatures reached in each experiment are shown in Table S2 †.…”
Section: Methodssupporting
confidence: 82%
“…Although some test cycles have been developed for brakes and tires, 36,51,53 there is no universally accepted protocol. There are a number of factors that impact emissions, including the velocity when the brakes are rst applied, the frequency and duration of braking, and the braking power and deceleration rate.…”
Section: Methodsmentioning
confidence: 99%
“…However, it was found that the NEDC test often did not reflect the conditions actually experienced when driving on public roads [50,51]. To improve the emissions and fuel consumption that occur when driving under road conditions, a new WLTP (World Harmonised Light Duty Procedure) driving test procedure was created [52]. With the new procedure, in addition to the determination of emissions during controlled driving tests with a chassis dynamometer, real driving emission (RDE) road tests are also carried out using mobile emission measurement systems -PEMS (Portable Emissions Measurement System) [53,54,55].…”
Section: Main Components Of Vehicle Exhaustmentioning
confidence: 99%
“…Brake-wear PM emissions account for up to ∼50% of nonexhaust PM 10 emissions and ∼20% of the total traffic-related PM 10 emissions. ,, Brake-wear processes exhibit a particularly high level of PM emissions at an aerodynamic diameter ranging from 2 to 6 μm (i.e., mode diameter of mass-weighted particle size distributions). , At a range of friction material temperature (i.e., 100–400 °C), previous studies found a shift of the mode diameter of mass-weighted particle size distributions toward a smaller size when the temperature decreased. , The characteristics of brake-wear PM emissions also vary with the type of friction materials (e.g., nonasbestos organic, semimetallic, low metallic, etc.) and operational conditions (e.g., vehicle speed, deceleration rate, and brake power). ,– …”
Section: Introductionmentioning
confidence: 99%